Impact sound ratings: ASTM versus ISO - Warnock, A.C.C. (Canadian Acoustics, 2004)
A comparison between the impact sound ratings of ASTM and ISO are discussed. When differences in these metrics are used to rank floor toppings, the rankings are inconsistent. To ISO 717 C50 rating, because of the low frequencies leads to unacce[tably large reproducibility ranges for tests on floors but should be acceptable for toppings. The C type ratings are not mandatory in ISO 717.